Verticalização das cidades brasileiras: uma desconstrução do espaço social - Ueda, Guilherme Shoiti (Universidade Federal de São Carlos, 2012)
The present work analyzes the process of verticalization of Brazilian cities, according to the concepts of territoriality, deconstruction space, social space. It examines the transformation of territory resulting from the vertical growth and densification of cities, from the point of view of the house and the territories of individuals and groups. Therefore, it is a bibliographical review on the relationship between man and space, which serves as the basis for a reading of the urban space, followed by bibliographic review on methods of urban analysis that used that approach. The period analyzed spans the entire history of the development of urban space in Brazil, focusing on the period of time in which the first vertical buildings appear in the capitals and cities of the country. The reading of the transformations, is empirically made through the analysis of several studies of other authors who address the subject in different Brazilian cities, in different periods. It is shown in the end, how the verticalization results in the isolation of individuals and the degradation of cities, and at the same time is influenced by changes occurring in society.
Keywords: Engenharia urbana; Territorialidade; Verticalização; Espaço social; Desconstrução espacial; Territoriality; Verticalization; Social space; Deconstruction; ENGENHARIAS